Moving beyond the language–Visualizing chemical concepts through one’s own creative expression - Adbo, Karina; AAkesson-Nilsson, Gunilla (Frontiers in Education, 2022)
The aim of the study was to explore university students’ interpretations of chemical content in the form of physical constructions of atomic nuclei. Playdough was chosen as the means for expression, since it provided the students with the task of choosing the number, form, size, shape, and distance of particles. Data was collected in the form of photographs, written explanations as well as ad hoc notes. Data from 64 students was analyzed using the three levels of analysis as presented by Hedegaard and framed within the theories of models. Results show that students’ choices gave rise to 34 variations of the atomic nuclei. The analysis provided two different categories: models with close resemblance to the teaching model and models with less resemblance to the teaching model. Results show the limitations of verbal and written communication and add to the discussion concerning students’ interpretations of the multitude of atomic models used in teaching. The method was indeed a beneficial tool both for students, who could explore the composition of atomic nuclei and isotopes, and for teachers, who could connect their teaching to students’ interpretations of scientific content since the method brings a new level of detail to discussions.